Protection of Women in Legal Cases: Objectivity of the Case Monitoring Process by Paralegals (Comparative Study of LBH APIK Semarang Indonesia and AWARE Singapore) - Ahmad Alif; Benjamin Laura (The Indonesian Journal of International Clinical Legal Education, 2022)
The presence of paralegals is like an oasis in the middle of a barren desert. The presence of paralegals especially in Indonesia is a new hope for those who want to obtain structural legal assistance (Bantuan Hukum Struktural, BHS), structural gender legal assistance (Bantuan Hukum Gender Struktural, BHGS) and clinical legal education. This study highlighted that paralegals from their point of view as human beings who have a subjective and objective side, especially in their role as paralegals in the Legal Aid Institute which is more involved with legal issues against women (LBH APIK Semarang). In its mission, LBH APIK Semarang to provide legal assistance and assistance for women who experience injustice, violence, and various forms of discrimination. As comparison, this study also found that, AWARE Singapore recognized as the leading women’s rights and gender equality group in Singapore. AWARE provides a feminist perspective in the national dialogue. It has effectively advocated against laws, public policies and mindsets that discriminate against women. AWARE has contributed towards the strengthening of laws dealing with domestic violence.